Analisis Kesalahan Fonologis Membaca Teks Bahasa Arab Siswa Madrasah Tsanawiyah Lampung Selatan - Amrulloh, Muhammad Afif; Hasanah, Haliyatul (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This study aims to find and reduce the location of errors in learning Arabic in the aspect of reciting Arabic letters (makhorijul letters) with the error analysis method. Focus more specifically on the phonetic aspect, namely on letters that sound like sounds. In addition, this study also aims to determine the forms of errors in reading Arabic texts in the phonological level (phonetic / makhroj aspects). This type of research is a qualitative study, conducted at MTs. Raudlatul Jannah Natar, South Lampung. Understanding the study of how to pronounce or sound Arabic letters is very important in learning Arabic to avoid pronunciation errors, so it does not hamper the learning process. The results of this study indicate that the forms of phonological errors that often occur when reading Arabic text activities are errors in sound in terms of articulation factors including among them: 1) apico-dental-alveolar sound. 2) Inter-dental sound. 3) Foronto-palatal sounds. 4) Dorso-uvular sound. 5) Dorso-velar sound. 6) Sound of avico-alveolars. 7) The sound of root-pharyngeals. The sound error in terms of aspects of articulation that is in: 1) fricative sound. 2) pop sound.